A Shoemaker Butterfly Prepona laertes (Lepidoptera: Nymphalidae) - James E. Hayden (EDIS)
Originally published on the Featured Creatures website at http://entnemdept.ufl.edu/creatures/bfly/Prepona_laertes.htm